Drug Safety - Case Reports - Joshi, Nitin; McMillan, Steve
Publishes case reports of individual and multiple patients experiencing adverse reactions to a wide range of medicinal products Reports include overdose, abuse, misuse, occupational exposure and more Also covers medication errors, off-label use and near-misses Drug Safety - Case Reports is an online, open access journal specialising in the publication of case reports and case series relating to suspected adverse drug reactions.  As well as reports of any unintended or adverse effects following administration of a medicinal product (or products), the journal welcomes reports of cases involving `near misses' (for example, medication errors detected before harm is done) and cases involving the lack of efficacy of a therapeutic product. Articles published in Drug Safety – Case Reports may be accompanied by plain language summaries to assist patients, caregivers  and others in their understanding. Upon acceptance for publication, manuscripts submitted to the journal will be subject to an article processing charge (APC) at an introductory price of US$1,095.  Adis Open Access enables you to make your journal article freely available to anyone, in exchange for payment of the APC. This option allows you, the author, to retain the copyright of the article according to the terms of the Creative Commons Attribution Non-Commercial (CC BY-NC) License, which does not permit commercial re-use of the article.